Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Saintifik pada Materi Struktur dan Fungsi Jaringan Tumbuhan - Zahara Citra; Asrial Asrial; Evita Anggereini (BIOEDUSAINS: Jurnal Pendidikan Biologi dan Sains, 2020)
This study aims to find out the effectiveness of the results of the development of scientific-based Learner Worksheets (LKPD) in improving critical thinking ability and to look at the development of worksheets in terms of feasibility, effectiveness, teacher response and student response. This research uses Research and Development (R & D) method to produce LKPD. The development model used in the research is the ADDIE model which consists of 5 stages namely analysis, design, development, planning and evaluation. The type of data used is skinative and quantitative data. Instruments used in the form of questionnaires and learning outcomes. The results of the study, from the validation results of material experts obtained a score of 84 with a good category and the results of validation media experts obtained a score of 90 with a very good category. The results of the teacher's response obtained a score of 93 with excellent categories and the correlation result of the teacher's response expressed a positive correlation to scientific-based LKPD. For learners to get a correlation value of 0.95, that means there is a strong correlation to scientifically based LKPD. While kappa test obtained by 0.60 with strong category. For effectiveness test if ρ value < 0.05 then H0 rejected, so Ha accepted. In conclusion, scientific-based LKPD effectively improves the critical thinking ability of learners, there are influences both before and after the use of worksheets developed in learning. Keywords: Development of LKPD, Scientific, Structure and Function of Plant Tissue